Multi-layer fabric laying method for improving interlayer bonding strength of carbon fiber material

Through the nanoparticle surface modification and segmented curing strategies, the interlayer bonding strength and mechanical properties of carbon fiber composite materials are improved, and the problem of insufficient interlayer shear strength in the prior art is solved, and is suitable for high-performance industrial applications.

CN119116406AActive Publication Date: 2024-12-13SUZHOU TITAN WIND POWER BLADE TECH CO LTD

Patent Information

Application Number
CN202411476753.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-13
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The lack of interlayer shear strength of existing carbon fiber composites leads to weakening of structure, limiting its application possibility under high mechanical load and high temperature environments.

Method used

By using carbon nanotubes or graphene sheets for chemical oxidation and functionalization of silane coupling agents, nanoreinforced resin is formed, and carbon fibers are weaved in a three-dimensional braiding machine, and segmented curing is carried out in combination with the resin transfer molding process to enhance interface stickiness to improve interface Adhesion and mechanical properties.

Benefits of technology

It significantly improves the interlayer bonding strength and overall structural integrity of carbon fiber materials, enhances the mechanical properties and thermal stability of the materials, and is suitable for high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116406A_ABST
    Figure CN119116406A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of high-performance composite materials, and discloses a multilayer fabric laying method for improving interlayer bonding strength of a carbon fiber material, which comprises the following steps: step 1, selecting carbon nanotubes or graphene sheets as nanoparticles, carrying out chemical oxidation treatment to introduce functional groups, and carrying out functionalization treatment by using a silane coupling agent; step 2, mixing the functionalized nano particles with epoxy resin in a high-shear-force mixing device to form uniform nano reinforced resin; and 3, weaving the carbon fibers according to a predetermined three-dimensional structure mode by using a three-dimensional weaving machine, and monitoring the fiber tension and the weaving density in real time in the weaving process. By using nanoparticles to reinforce the composite material and carrying out chemical oxidation and coupling agent functionalization treatment, the interface adhesive force between the carbon fibers and the epoxy resin is improved, functional groups can form stronger chemical bonds with the resin, the interlaminar shear strength of the composite material is improved, and the overall structural integrity and durability of the material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of high-performance composite materials, and in particular to a multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials. Background Art

[0002] In modern industry, especially in the fields of aerospace, automotive manufacturing and sports equipment, the demand for high-performance composite materials is growing. These materials need to have excellent mechanical strength, heat resistance and excellent structural integrity to meet demanding application requirements. Carbon fiber composite materials are widely used in these fields due to their light weight and high strength. Their performance advantages are of great significance to improving product performance and energy efficiency.

[0003] In the prior art, the preparation of carbon fiber composites mainly relies on traditional resin-based composite processes, such as hand lay-up, vacuum bag compression and resin transfer molding (RTM). In these methods, the combination of carbon fiber and resin is usually achieved through simple mechanical mixing, and the curing process of the resin is often carried out under relatively simple conditions, such as a single curing temperature and pressure.

[0004] However, the existing technology has limitations in the interfacial adhesion between carbon fiber and resin, which directly affects the interlaminar shear strength of the composite material. Due to the lack of interfacial adhesion, the composite material is prone to interlaminar separation when subjected to tension or shear force, resulting in the weakening of the overall structure. This problem limits the possibility of composite materials being used in environments that need to withstand large mechanical loads or in high temperature environments, affecting the wide application and long-term reliability of the material. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a multi-layer fabric laying method for improving the bonding strength between layers of carbon fiber materials, thereby solving the problem of insufficient shear strength between layers of composite materials in the prior art.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials comprises the following steps:

[0007] Step 1: Select carbon nanotubes or graphene sheets as nanoparticles, perform chemical oxidation treatment to introduce functional groups, and use a silane coupling agent for functionalization treatment;

[0008] Step 2: mixing the functionalized nanoparticles with epoxy resin in a high shear mixing device to form a uniform nano-enhanced resin;

[0009] Step 3: Use a 3D braiding machine to weave the carbon fiber according to a predetermined 3D structural pattern, and monitor the fiber tension and weaving density in real time during the weaving process;

[0010] Step 4: Inject the nano-reinforced resin into the pre-woven carbon fiber structure under controlled temperature and pressure conditions through a resin transfer molding process, and cure it at multiple temperature and pressure stages.

[0011] Preferably, the chemical oxidation treatment is carried out at a temperature controlled at 40° C. to 60° C., and the treatment time is 1 to 3 hours.

[0012] Preferably, the silane coupling agent is 3-aminopropyltriethoxysilane, the mass ratio of the silane coupling agent to the nanoparticles is 1:10, and the functionalization treatment time is controlled within 2 to 4 hours.

[0013] Preferably, the mixing of the nanoparticles and the epoxy resin is carried out using a high-energy ball mill, the ball milling time is 30 to 60 minutes, and the ball milling speed is set to 500 to 800 rpm.

[0014] Preferably, the nano-reinforced resin mixture is subjected to a vacuum degassing treatment for at least 15 minutes immediately after mixing, and the vacuum pressure is -0.1 MPa.

[0015] Preferably, the three-dimensional braiding machine is equipped with an automatic tension adjustment system controlled by a microprocessor to ensure the consistency of fiber tension during the braiding process.

[0016] Preferably, the braiding parameters include a fiber tension set at 200 to 500 Newtons, a braiding density of not less than 15 strands of fiber per square centimeter, and a layer thickness adjusted according to the design requirements of the final structural component.

[0017] Preferably, the resin transfer molding process includes a low-pressure pre-injection stage and a high-pressure full injection stage to ensure complete infiltration and defect-free filling of the resin.

[0018] Preferably, the curing process adopts staged temperature control, with the initial curing stage lasting for 2 hours at 80° C., and then increasing to 150° C. and maintaining for 1 hour.

[0019] Preferably, the method further comprises evaluating the microstructure of the obtained composite material using a scanning electron microscope.

[0020] The present invention provides a multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials. It has the following beneficial effects:

[0021] 1. The present invention significantly improves the interfacial adhesion between carbon fiber and epoxy resin by using nanoparticles to reinforce composite materials and subjecting these particles to chemical oxidation and coupling agent functionalization treatment. This interface optimization is achieved by introducing functional groups on the surface of nanoparticles, which can form stronger chemical bonds with the resin, and the interlaminar shear strength of the composite material is significantly improved, thereby enhancing the overall structural integrity and durability of the material.

[0022] 2. The present invention not only improves the interfacial adhesion by uniformly distributing surface-modified nanoparticles in the composite material, but also significantly improves the mechanical properties of the material, such as tensile strength and modulus, through the nano-enhancement effect. The introduction of these nanoparticles enables the composite material to maintain or even improve its elasticity while bearing higher loads, which is particularly important for high-performance applications such as aerospace, automobiles and sports equipment.

[0023] 3. The staged curing strategy adopted by the present invention helps to optimize the microstructure of the composite material, especially its performance at high temperatures. By first allowing the resin to gradually cure at a lower temperature and then increasing the temperature to enhance the crosslinking density of the material, the present invention ensures that the composite material maintains excellent mechanical properties and dimensional stability at higher operating temperatures. This improved thermal stability is particularly important for applications that may be exposed to extreme environmental conditions, such as the high temperature environments often encountered in the aerospace field.

[0024] 4. By using a high-precision 3D braiding machine and a finely controlled RTM process, the present invention can ensure that each layer of fiber is evenly distributed and cured under precisely controlled conditions, thereby improving the repeatability of the entire manufacturing process and the consistency of product quality. The controllability of this process is crucial for the large-scale production of high-performance carbon fiber composites, ensuring product reliability and production efficiency.

[0025] By combining the above points, the present invention significantly improves the overall performance of carbon fiber composite materials, including mechanical strength, heat resistance and structural stability. These performance improvements make the composite materials of the present invention more suitable for demanding industrial applications, especially those fields that require lightweight and high-strength materials, thereby broadening its market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] Please see attached Figure 1 The embodiment of the present invention provides a multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials, comprising the following steps:

[0030] Advanced selection and surface modification of nanoparticles:

[0031] In this example, carbon nanotubes and graphene sheets were selected for reinforcing composites, mainly because of their high specific surface area and excellent mechanical properties, especially in terms of tensile strength and modulus. Conventional composites are often limited by non-uniform distribution and weak interfacial adhesion at the microscopic scale, while these nanomaterials can significantly improve interfacial adhesion.

[0032] Chemical oxidation treatment: A mixed solution of sulfuric acid and nitric acid with a concentration of 3:1 was used to oxidize carbon nanotubes and graphene sheets. The reaction was carried out under temperature control conditions, with the temperature controlled at 50°C and the duration lasting for 3 hours. This treatment method can effectively introduce functional groups such as carboxyl and hydroxyl groups on the surface of nanoparticles, enhancing their binding force with epoxy resin.

[0033] Silane coupling agent functionalization treatment: APTES was selected as the coupling agent for surface functionalization. This process was carried out at room temperature. The coupling agent and nanoparticles were mixed in a ratio of 1:10 to ensure that the surface of each nanoparticle was evenly covered with the coupling agent, thereby improving its dispersibility and interfacial bonding in the epoxy resin.

[0034] Preparation of Nano-enhanced Resins

[0035] Resin mixing and degassing:

[0036] High shear mixing: When preparing the resin, a high shear mixer is used, which can generate sufficient shear force at high speed to evenly disperse the nanoparticles in the resin. The mixing process is controlled at 50°C to prevent premature curing of the resin and ensure uniform mixing, and the mixing time is 40 minutes.

[0037] Vacuum degassing: The mixed resin is immediately vacuum degassed to remove the air introduced during the mixing process. This step is carried out in a dedicated vacuum degassing device for 20 minutes, with a vacuum degree of -0.1MPa. This is a key step to ensure the density and final performance of the composite material.

[0038] 3D weaving and RTM technology

[0039] Application of high precision 3D knitting machine:

[0040] Using a high-precision 3D braiding machine, the machine is equipped with a sophisticated braiding control system that can accurately adjust the fiber tension and braiding density to ensure that each layer of fiber is evenly distributed. In addition, the braiding parameters such as fiber tension controlled at 300 Newtons and braiding density of 20 strands of fiber per square centimeter are critical to ensuring the consistency and performance of the material structure.

[0041] RTM process: Nano-reinforced resin is injected into the woven carbon fiber structure under precisely controlled pressure and temperature conditions through the RTM process. The RTM process includes low-pressure pre-injection and high-pressure full injection stages, using advanced control systems to ensure that the resin completely impregnates the carbon fiber and optimizes the material's microstructure and interlayer strength.

[0042] Optimization of curing strategy:

[0043] The curing process adopts a segmented temperature control strategy, first with an initial curing at 80°C for 2 hours to allow the resin to cure slowly and reduce internal stress; the temperature is then raised to 150°C and maintained for 1 hour to enhance the crosslinking density of the material and improve its ultimate mechanical properties and heat resistance.

[0044] Performance Evaluation

[0045] Detailed microstructure and performance evaluation:

[0046] Scanning electron microscopy (SEM) was used to evaluate the microstructure of the composite in detail, especially the distribution of nanoparticles in the resin matrix and their interfacial bonding. This analysis helped verify whether the dispersion of the nanoparticles and the interfacial bonding properties met the expectations.

[0047] Dynamic Mechanical Analysis (DMA) is used to evaluate the viscoelastic properties of composites under different temperature and load conditions to fully understand how the material will perform in real-world applications.

[0048] Embodiment 2:

[0049] The second embodiment provides a preferred method for laying multi-layer fabrics to improve the interlayer bonding strength of carbon fiber materials, comprising the following steps:

[0050] Surface pretreatment of carbon fiber

[0051] In this embodiment, the main purpose of the surface pretreatment is to improve the interfacial adhesion between the carbon fibers and the nano-reinforced resin, thereby increasing the mechanical strength and durability of the final composite material.

[0052] Chemical oxidation of carbon fiber:

[0053] Operation steps: First, soak the carbon fiber in a solution containing an oxidant, usually hydrogen peroxide as a mild oxidant. The treatment temperature of the carbon fiber in the hydrogen peroxide solution is 60°C and the duration is set to 1 hour. The selection of this temperature and time is based on the results of experimental optimization, aiming to effectively introduce functional groups on the surface of the carbon fiber without damaging its basic structure.

[0054] Introduction of functional groups: This step introduces carboxyl (-COOH) and hydroxyl (-OH) groups on the fiber surface by chemical oxidation. These functional groups can significantly enhance the chemical bonding potential between the fiber and the resin, providing stronger interfacial adhesion.

[0055] Coupling agent treatment:

[0056] Choose a suitable coupling agent: Choose APTES as the coupling agent, which can react with the functional groups on the fiber surface to form stable chemical bonds, thereby improving the compatibility between the fiber and the resin.

[0057] Treatment process: The oxidized carbon fiber is immersed in a solution containing APTES. This treatment is carried out at room temperature and the reaction time is controlled to 3 hours to ensure that the coupling agent fully covers the surface of each fiber.

[0058] Optimization of weaving and RTM processes

[0059] Control of weaving process:

[0060] Technical details: The fibers are woven using an advanced 3D braiding machine. The braiding machine is equipped with a precise control system that can adjust the fiber tension and braiding density in real time. In this embodiment, the braiding density is set to 20 strands of fiber per square centimeter, and the tension is maintained at 300 Newtons to ensure uniformity and consistency of the braiding.

[0061] Implementation of RTM process:

[0062] Adjustment of pressure and speed: During the RTM process, low-pressure pre-injection (pressure 0.3MPa) is first performed to ensure the initial distribution of the resin, and then the injection is completed at high pressure (1.5MPa) to ensure that the resin completely penetrates the carbon fiber structure. This phased injection strategy is optimized based on experimental data to achieve the best resin flow and filling effect.

[0063] Through such detailed technical description and step implementation, the preferred embodiment 2 not only discloses the surface pretreatment process of carbon fiber and its optimized weaving and RTM process, but also provides specific operating conditions and parameters. This ensures the complete reproducibility of the technical solution and helps to achieve the expected high performance requirements in practical applications.

[0064] Embodiment three:

[0065] This embodiment provides a multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials, comprising the following steps:

[0066] Surface modification of nanoparticles using different coupling agents

[0067] Advanced selection and surface modification of nanoparticles:

[0068] In this embodiment, carbon nanotubes and graphene sheets are also selected as reinforcing agents for the same reasons as in the first embodiment: their high specific surface area and excellent mechanical properties.

[0069] Chemical oxidation treatment: Same as in Example 1, a mixed solution of sulfuric acid and nitric acid with a concentration of 3:1 was used for treatment. The reaction was carried out under temperature control conditions at 50° C. and lasted for 3 hours.

[0070] Changes in coupling agent functionalization:

[0071] Use of different coupling agents: In this example, a silane coupling agent KH-550 (γ-aminopropyltriethoxysilane) was selected instead of APTES. The mixing ratio of the coupling agent and the nanoparticles was the same as in Example 1, but KH-550 provided different chemical functionality, which may affect the interface bonding and dispersibility of the final composite material.

[0072] Preparation, 3D weaving and RTM process of nano-reinforced resin:

[0073] Resin mixing and degassing: As in Example 1, a high shear mixer is used for mixing at a controlled temperature and a vacuum degassing treatment is performed.

[0074] Three-dimensional weaving and RTM process: The same high-precision three-dimensional weaving machine and RTM process as in Example 1 are used to ensure the uniformity and consistency of the composite material.

[0075] Curing strategy and performance evaluation:

[0076] Curing strategy: The same segmented temperature control strategy as in Example 1 was adopted, with initial curing at 80° C. for 2 hours, and then the temperature was raised to 150° C. and maintained for 1 hour.

[0077] Performance evaluation: The same detailed microstructure and performance evaluation as in Example 1 was performed using SEM and DMA to compare the effects of different coupling agents.

[0078] It is expected that the carbon fiber composite material using KH-550 as a coupling agent may be slightly inferior to Example 1 using APTES in terms of interfacial adhesion. This is because the chemical structure and functional groups of KH-550 may have different reaction efficiencies with the surface functional groups of carbon nanotubes and graphene sheets, thereby affecting the final bonding effect of nanoparticles and epoxy resin.

[0079] Embodiment 4:

[0080] This embodiment provides a multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials, comprising the following steps:

[0081] Carbon fiber composites with optimized fiber weaving density

[0082] Nanoparticle selection and surface modification

[0083] Similar to the first embodiment, carbon nanotubes and graphene sheets are selected for chemical oxidation treatment and silane coupling agent functionalization treatment to ensure that the surface of the nanoparticles has appropriate functional groups to enhance the binding force with the epoxy resin.

[0084] Preparation of Nano-enhanced Resins

[0085] The mixing and degassing process of the resin remained unchanged, using a high shear mixer at 50°C for 40 minutes, followed by vacuum degassing to ensure the homogeneity and density of the resin.

[0086] Optimization of weaving parameters

[0087] Adjustment of weaving density:

[0088] In Example 4, the weaving density of the fibers was adjusted from 20 strands of fibers per square centimeter in Example 1 to 15 strands of fibers per square centimeter. This adjustment was intended to explore the effect of lower weaving density on the mechanical properties of the material, especially the interlayer bonding strength.

[0089] Using the same 3D braiding machine, the fiber tension is kept at 300 Newtons to ensure uniform fiber distribution and tension consistency during the braiding process.

[0090] RTM process and curing strategy

[0091] The same RTM process as in Example 1 is used, including low-pressure pre-injection and high-pressure full-injection stages, and the same curing temperature control strategy.

[0092] Performance Evaluation

[0093] The microstructure and properties of the finished composites were evaluated using scanning electron microscopy (SEM) and dynamic mechanical analysis (DMA), with a particular focus on the effect of changes in weave density on the composite properties.

[0094] It is expected that the lower weave density in Example 4 may result in a slight reduction in the interlaminar bonding strength of the composite material, as the looser weave structure may not be sufficient to provide the same level of fiber-resin interface contact as in Example 1. This change will provide key insights into the impact of weave density on the performance of carbon fiber composites, especially the importance of interlaminar bonding in high-performance applications.

[0095] Table 1 Comparison table of experimental data of embodiment

[0096]

[0097] Example 1 shows the best performance index among all the examples, indicating that the use of APTES coupling agent combined with high-density weaving parameters can effectively improve the overall performance of carbon fiber composite materials.

[0098] The performance of Example 2 is slightly lower than that of Example 1, which may be because the surface pretreatment of the carbon fibers is not as significant as the APTES treatment in improving the interfacial adhesion.

[0099] The performance degradation of Example 3 using a different coupling agent (KH-550) may be attributed to the different chemical reaction efficiencies between the coupling agent and the nanoparticles, which affects the interfacial bonding force.

[0100] The performance of Example 4 is further reduced, which is related to the lower weaving density, showing the important influence of the density of the weaving structure on the material properties, especially the reduction in the interlaminar shear strength.

[0101] Comparative Example 1:

[0102] This comparative example discloses a conventional multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials, comprising the following steps:

[0103] Carbon Fiber Treatment:

[0104] No chemical oxidation or coupling agent functionalization treatment was performed, and the carbon fibers were only basically cleaned and dried to remove surface impurities.

[0105] Resin Mixing:

[0106] Standard epoxy resin was used without any nanoparticles added. The resin mixing process involved only simple mechanical stirring to ensure uniform composition.

[0107] Weaving and RTM process:

[0108] The carbon fibers are mechanically woven at a low weave density, set at 15 strands per square centimeter, without precise tension control.

[0109] The RTM process is relatively simple, involving only a single pressure stage of resin injection without detailed temperature and pressure control.

[0110] Curing process:

[0111] Single temperature curing, usually at 100°C for 2 hours, without multi-stage temperature control strategy.

[0112] Performance Evaluation

[0113] Microstructure and properties:

[0114] Without specific microstructural evaluation, material properties are often evaluated relying solely on basic mechanical testing, such as tensile and flexural testing.

[0115] Table 2 Comparative Example Experimental Data Table

[0116] Embodiment 1 Comparative Example 1 Interlaminar shear strength (MPa) 68 45 Tensile strength(MPa) 2500 1800 Modulus(GPa) 230 150 DMA temperature resistance (℃) 180 1220

[0117] The performance of the conventional comparative example is significantly lower than that of Example 1, especially in terms of interlaminar shear strength and tensile strength. This indicates that the reinforcing effect of nanoparticles and fine surface treatment are crucial to improving the performance of composite materials.

[0118] The DMA temperature resistance of the conventional method is also low, which may be due to the insufficient curing of the resin and the lack of microstructure optimization brought by nanoparticles.

[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials, characterized in that: The following steps are involved: Step 1: Select carbon nanotubes or graphene sheets as nanoparticles, perform chemical oxidation treatment to introduce functional groups, and use a silane coupling agent for functionalization treatment; Step 2: mixing the functionalized nanoparticles with epoxy resin in a high shear mixing device to form a uniform nano-enhanced resin; Step 3: Use a 3D braiding machine to weave the carbon fiber according to a predetermined 3D structural pattern, and monitor the fiber tension and weaving density in real time during the weaving process; Step 4: Inject the nano-reinforced resin into the pre-woven carbon fiber structure under controlled temperature and pressure conditions through a resin transfer molding process, and cure it at multiple temperature and pressure stages.

2. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The chemical oxidation treatment is carried out at a temperature controlled at 40° C. to 60° C., and the treatment time is 1 to 3 hours.

3. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane, the mass ratio of which to the nanoparticles is 1:10, and the functionalization treatment time is controlled within 2 to 4 hours.

4. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The nanoparticles and the epoxy resin are mixed using a high-energy ball mill, the ball milling time is 30 to 60 minutes, and the ball milling speed is set to 500 to 800 rpm.

5. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The nano-enhanced resin mixture is immediately subjected to a vacuum degassing treatment for at least 15 minutes after mixing, with a vacuum pressure of -0.1 MPa.

6. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The three-dimensional braiding machine is equipped with a microprocessor-controlled automatic tension adjustment system to ensure the consistency of fiber tension during the braiding process.

7. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 6, characterized in that: The weaving parameters include fiber tension set at 200 to 500 Newtons, a weaving density of no less than 15 strands of fiber per square centimeter, and layer thickness adjusted according to the design requirements of the final structural components.

8. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The resin transfer molding process includes a low-pressure pre-injection stage and a high-pressure full injection stage to ensure complete resin infiltration and defect-free filling.

9. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The curing process adopts segmented temperature control. The initial curing stage lasts for 2 hours at 80°C, and then increases to 150°C and maintains for 1 hour.

10. The multi-layer fabric laying method for improving the interlayer bonding strength of carbon fiber materials according to claim 1, characterized in that: The method further comprises evaluating the microstructure of the composite material using a scanning electron microscope.

Citation Information

Patent Citations

  • Forming method of 2.5-dimensional weaving revolving solid composite material

    CN101811365A

  • Preparation method of carbon fiber / carbon nanotube / organic silicone resin multidimensional hybrid composite material

    CN104151827A

  • Preparation method of carbon fiber / graphene / epoxy resin prepreg and carbon fiber composite material

    CN105968718A

  • Molding apparatus, and method for manufacturing base material

    JP2020183059A

Cited By

  • Graphene composite conductive material and preparation method thereof

    CN119673528A

  • Continuous fiber reinforced composite material for stent-free inflatable gas film and preparation method of continuous fiber reinforced composite material

    CN120209366A